That all may believe: a theology of the Gospel and the mission of the church - Braaten, Carl E. (William B. Eerdmans Pub, 2008)
Doing theology Pro Ecclesia -- Evangelical and Catholic theology -- Christ the center of ecumenical orthodoxy -- Revelation through creation and the Gospel -- The unity of Scripture -- Theology -- The interpretation of the Bible in the church -- Sola scriptura versus partim-partim -- The authority of the Bible reconsidered -- An open question -- The role of dogma in church and theology -- Theology without dogma and dogmatics -- Reclaiming dogma for the church -- Catholics and Lutherans : being and becoming church together -- The question of Lutheran identity -- Catholic-Lutheran relations since Vatican II -- The joint declaration on the Doctrine of Justification -- Paul Tillich on the "Protestant principle and Catholic substance" -- Paul Tillich's self-understanding -- The meaning of "Protestant principle" -- The meaning of "Catholic substance" -- Gospel -- The Gospel proviso : paradigms of theology in conflict -- Paradigm #1: Albert Schweitzer and the quest of the historical Jesus -- Paradigm #2: Adolf von Harnack and the essence of Christianity -- Paradigm #3: Karl Barth on the otherness of God and his unique revelation -- Paradigm #4: Rudolf Bultmann a nd the hermeneutical question -- Paradigm #5: Wolfhart Pannenberg and the historicity of the Resurrection -- Paradigm #6: The Holocaust and the canonicity of the Old Testament -- Paradigm #7: Liberation theology and the freedom of the Gospel -- Paradigm #8: The Second Vatican Council and the ecumenical movement -- The resurrection debate revisited -- The irony of the scholarly consensus -- The place of the resurrection in the history of Christian thought -- Misinterpretations of the resurrection -- The current shape of the resurrection debate -- Elements of a theology of the resurrection -- Powers in conflict : Christ and the devil -- Does the devil really exist? -- The devil in the Bible and the Christian tradition -- Current manifestations of the demonic -- Discerning the spirits -- Nullus diabolus, nullus redemptor -- The recovery of apocalyptic imagination -- The apocalyptic Jesus -- Cross and resurrection : the fulcrum of history -- The good news of the apocalypse mission -- Reclaiming the missionary nature of the church -- The legacy of christendom -- Re-evangelizing in the post-modern situation -- Toward an ecumenical missiology -- Hearing the other : the problem and promise of pluralism -- Models : exclusivism, inclusivism, pluralism -- The exclusivity of Christ -- The inclusiveness of the Gospel -- The Christian mission among Muslims -- Old Testament perspectives on mission -- The historical Jesus and mission -- The missionary proclamation of the Apostles -- The hope of salvation